2010
DOI: 10.1159/000319892
|View full text |Cite
|
Sign up to set email alerts
|

Stroke History and Chagas Disease Are Independent Predictors of Silent Cerebral Microembolism in Patients with Congestive Heart Failure

Abstract: Background: Chagas disease is endemic in South and Central America, where 18 million individuals are infected by Trypanosoma cruzi, causing congestive heart failure (CHF) and cardioembolic stroke. Transcranial Doppler (TCD) is able to detect real-time microembolic signals (MES) to the brain vessels and may represent a surrogate marker of stroke risk. We aimed to determine predictors of MES in a population of patients with CHF. Methods: Consecutive CHF patients from a university-based cardiomyopathy clinic unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…al. demonstrated an independent relationship between the signs of microembolism on transcranial Doppler and the history of stroke in patients with Chagas disease 25 . These data further corroborate the hypothesis that several risk factors are involved in addition to those already elucidated.…”
Section: Stroke In the Setting Of Chagas Disease: An Overview Of Prev...mentioning
confidence: 93%
“…al. demonstrated an independent relationship between the signs of microembolism on transcranial Doppler and the history of stroke in patients with Chagas disease 25 . These data further corroborate the hypothesis that several risk factors are involved in addition to those already elucidated.…”
Section: Stroke In the Setting Of Chagas Disease: An Overview Of Prev...mentioning
confidence: 93%
“…Also, microembolic signals occurred independently of left ventricle function in chagasic patients. The authors speculate alternative mechanisms, besides heart failure, to explain microemboli, such as some kind of inflammatory reaction [41]. As we know that silent microemboli may be related to increased risk of ischemic stroke, it is an indirect demonstration of a greater stroke risk among chagasic patients.…”
Section: Chagas Disease and Strokesmentioning
confidence: 99%
“… 18 Jesus et al, searching for signs of microemboli on transcranial Doppler in a cardiomyopathy clinic, showed that microemboli are more frequent among patients with CCC compared to patients with other heart diseases, independent of left ventricle function, and are also associated with silent heart attacks. 19 Silent brain infarcts have also been described by another author. 10 It is speculated that inflammation 18 and thrombogenic factors 20 play a role in this mechanism, but these need to be further clarified.…”
Section: Introductionmentioning
confidence: 84%